2011
DOI: 10.4028/www.scientific.net/amr.199-200.638
|View full text |Cite
|
Sign up to set email alerts
|

Oil Droplet Motion Considering Breakup in an Aeroengine Bearing Chamber

Abstract: Oil droplets can break up during flight and form many secondary droplets in an aero-engine bearing chamber due to aerodynamic drag forces. The motion properties of secondary droplets have significant influence on the two-phase oil/air flow phenomena in bearing chambers. In this work, oil droplet trajectories and velocities are developed by accounting for in-flight breakup. The droplet motion is modelled using a Lagrangian tracking method, and the trajectories and velocities are calculated by numerical integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Some droplets can travel suspended within the convective air before they escape through the vent lines (Farrall et al, 2006); others can splash onto the walls of the chamber (Peduto, 2015) or might break up before coming into contact with the walls. In both splashing and breakup, there is the formation of smaller droplets called secondary droplets (Chen et al, 2011a), as indicated schematically in Figure 2.1.…”
Section: Oil Droplets In Bearing Chambersmentioning
confidence: 99%
See 4 more Smart Citations
“…Some droplets can travel suspended within the convective air before they escape through the vent lines (Farrall et al, 2006); others can splash onto the walls of the chamber (Peduto, 2015) or might break up before coming into contact with the walls. In both splashing and breakup, there is the formation of smaller droplets called secondary droplets (Chen et al, 2011a), as indicated schematically in Figure 2.1.…”
Section: Oil Droplets In Bearing Chambersmentioning
confidence: 99%
“…Henceforth, the secondary droplets' size distribution can be determined by the Sauter mean diameter (SMD) and mass median diameter (MMD). The secondary droplet diameter is given by Chen et al (2011a) as follows:…”
Section: Droplet Break-up and Deformationmentioning
confidence: 99%
See 3 more Smart Citations